Production of a minimally processed jelly candy for children using honey instead of sugar. (July 2018) - Mutlu, Ceren; Tontul, Sultan Arslan; Erbaş, Mustafa
Abstract: This study investigated some chemical, physical and sensorial properties of honey jelly candies made by two different mixing techniques (cold and hot), three gelatine doses (15, 20 and 25% of honey weight) and three fruit juices (orange, strawberry and black mulberry). The mean water content and activity of samples were 23.38% and 0.73, respectively. The acidity and diastase number of samples ranged between 40.12 and 46.09 meq/kg and 15.43–0.00, respectively. While diastase activity of honey was preserved more than 95% by cold mixing technique in candy form, it was completely lost in the hot mixing technique. Increasing of gelatine dose, increased the hardness, adhesiveness, chewiness and gumminess values of candies. Additionally, the glucose, fructose and sucrose contents of cold mixed honey jelly candies were determined as 403.23 ± 5.24, 491.10 ± 7.61 and 1.38 ± 0.12 g/kg, respectively. Addition of fruit juices increased the acidity value and sugar and proline contents of samples. The sensorial acceptability score for honey jelly candies obtained more than 3.5 on a 5-point hedonic scale. In conclusion, a new jelly candy as a healthier alternative to the existing ones was produced by minimal processing with honey and fruit juices instead of sugar syrup and artificial additives without inactivation of bioactive compounds of honey. Highlights: Two mixing methods (cold and hot), three gelatine rates (15, 20, 25%) were studied. Cold mixing technique protected diastase enzyme activity more than 95%. Sugar and proline contents of cold mixed samples were higher than hot mixed samples. Cold mixed sample with 15% gelatine rate was selected as the best candy. Selected candy was reproduced by fresh orange, strawberry and black mulberry juices.